(untitled) (Indo-American Journal of Life Sciences and Biotechnology, 2020)
The goal of this study is to determine how theacrine affects the development of sepsis and the severity of lung damage caused by sepsis. Methods: The mice were given injections of 3 mg/kg LPS dissolved in 50 μL PBS or only PBS (control group = 10), creating a lung damage model of lipopolysaccharide (LPS)-induced sepsis. One hour after LPS treatment, theacrine was orally gavaged to the other three groups of mice (ten mice per group) at doses of 10, 20, and 40 mg/kg, respectively. The impact of theacrine on lung damage was confirmed by hematoxylin and eosin (H&E) staining. We measured oxidative stress and inflammatory factors using enzyme-linked immunosorbent assays (ELISA) and quantitative polymerase chain reactions (qPCR). The impact on apoptosis and mechanism of action were confirmed using TUNEL and immunoblot tests. Results: In mice with LPS-induced sepsis, theacrine had a significant impact on lung injury and lung relief score (p < 0.01). It also reversed the increased levels of inflammatory cytokines in a dose-dependent manner (p < 0.01). Furthermore, theacrine significantly reduced the intensity of increased levels of ROS and MDA, and improved the levels of SOD in lung tissues (p < 0.01). In addition, it reduced lung damage and enhanced LPS-induced cell death in the lungs via activating the SIRT3 pathway (p < 0.01). Results: Theacrine reduces inflammation and lung damage in septic mice by modulating SIRT3, suggesting it may be a promising therapeutic development lead for sepsis-related lung injury and inflammation. Tags: SIRT3 pathway, oxidative stress, sepsis, lung damage, theacrine